Effect of CaO on retention of S, Cl, Br, As, Mn, V, Cr, Ni, Cu, Zn, W and Pb in bottom ashes from fluidized-bed coal combustion power station - Bartoňová, Lucie; Klika, Zdeněk (Journal of environmental sciences (China), 2014)
This work was conducted to evaluate whether Ca-bearing additives used during coal combustion can also help with the retention of some other elements. This work was focused on the evaluation of bottom ashes collected during four full-scale combustion tests at an operating thermal fluidized-bed power station. Bottom ashes were preferred to fly ashes for the study to avoid interference from condensation processes usually occurring in the post-combustion zone. This work focused on the behaviors of S, Cl, Br, As, Mn, V, Cr, Ni, Cu, Zn, W, and Pb. Strong positive correlations with CaO content in bottom ashes were observed (for all four combustion tests) for S, As, Cl and Br (R=0.917-0.999). Strong inverse proportionality was calculated between the contents of Pb, Zn, Ni, Cr and Mn and CaO, so these elements showed association to materials other than Ca-bearing compounds (e.g., to aluminosilicates, organic matter, etc.). Somewhat unclear behaviors were observed for W, Cu, and V. Their correlation coefficients were evaluated as statistically "not significant", i.e., these elements were not thought to be significantly associated with CaO. It was also discovered that major enrichment of CaO in the finest bottom ash fractions could be advantageously used for simple separation of elements strongly associated with these fractions, mainly S and As, but also Cl or Br. Removal of 5% of the finest ash particles brings about a decrease in As concentration down to 77%-80% of its original bulk ash content, which can be conveniently used e.g., when high As content complicates further ash utilization.
Keywords: velikost částic; Particle Size; popel uhelný; Calcium Compounds; oxidy; Metals; Oxides; sloučeniny vápníku; kovy; Coal Ash